2016
DOI: 10.2337/dc16-1565
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Socioeconomic Status in Predicting Metabolic Syndrome and Glucose Abnormalities in Adulthood: The Cardiovascular Risk in Young Finns Study

Abstract: Lower SES in childhood may be associated with an increased risk for MetS, IFG, and type 2 diabetes in adulthood. Special attention could be paid to children of low SES families to decrease the prevalence of MetS in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 40 publications
(43 reference statements)
2
41
0
Order By: Relevance
“…The association between socioeconomic position in childhood and subsequent CVD risk in adulthood is now well established, with a considerable body of evidence showing markers of low socioeconomic status in childhood to be associated with CVD risk factors (Kivimaki, Smith, Juonala, et al, 2006), metabolic syndrome (Puolakka et al, 2016), vascular structure and function (Kivimaki, Lawlor, et al, 2006; Kivimaki, Smith, Elovainio, et al, 2006; Kivimaki, Smith, Juonala, et al, 2006; Puolakka et al, 2017) and risk of coronary heart disease (Lawlor, Smith, & Ebrahim, 2004). Less evidence exists for associations with psychosocial adversity in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The association between socioeconomic position in childhood and subsequent CVD risk in adulthood is now well established, with a considerable body of evidence showing markers of low socioeconomic status in childhood to be associated with CVD risk factors (Kivimaki, Smith, Juonala, et al, 2006), metabolic syndrome (Puolakka et al, 2016), vascular structure and function (Kivimaki, Lawlor, et al, 2006; Kivimaki, Smith, Elovainio, et al, 2006; Kivimaki, Smith, Juonala, et al, 2006; Puolakka et al, 2017) and risk of coronary heart disease (Lawlor, Smith, & Ebrahim, 2004). Less evidence exists for associations with psychosocial adversity in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adults with low SES are more likely to have a poor diet, low levels of physical activity (PA) and high levels of sedentary behaviours and therefore, they show higher rates of obesity and diabetes than children and adults with high SES [7]. Higher SES in childhood has been associated with a lower risk for MetS more than 30 years later in adulthood independently of cardiometabolic risk factors in childhood and participants' SES in adulthood [8]. These results emphasize that obesity and MetS tracks into adulthood [9].…”
Section: Introductionmentioning
confidence: 99%
“…We found that obesity in childhood, low SES, parental CVD history and short sleep duration are significant risk factors for CVD-RFC in adolescents. Previous prospective cohort studies suggested that anthropometric measurements,23 childhood SES,24 childhood nutrition,15 some biochemical markers such as BP, lipid profiles and insulin level and family history of hypertension and diabetes25 were youth determinants of adult MetS.…”
Section: Discussionmentioning
confidence: 99%